A proposal of a “ready to use” COVID-19 control strategy in an Oncology ward: Utopia or reality? - Dalu, Davide; Rota, Selene; Cona, Maria Silvia; Brambilla, Anna Maria; Ferrario, Sabrina; Gambaro, Anna; Meroni, Luca; Merli, Stefania; Farina, Gabriella; La Verde, Nicla (Critical reviews in oncology/hematology, 2021)
[Display omitted] •During COVID-19 pandemic cancer patients are a vulnerable category.•Few data about control infection strategy to ensure a COVID-19 free Oncology ward.•The essence of our protocol: triage, risk zones, traffic control and surveillance.•This strategy could be a practical contribution to control nosocomial COVID-19. The Coronavirus Disease-2019 (COVID-19) pandemic is spreading in Italy and Lombardy is one of the most affected region. Cancer patients are higher risk of complication from COVID-19 complications; therefore they should be protected from contagion while still ensuring access to cancer care. The aim of this article is to suggest a strategy to reorganize hospital spaces and Healthcare Professionals (HCPs) staff in order to avoid COVID-19 nosocomial infection in an Oncology ward. SARS-CoV-2 is primarily transmitted through respiratory droplets and by contact. We speculated that precautions against droplet and contact transmission should be the proper way to preserve ward from COVID-19. The essence of our protocol involves: triage outside of the ward, identification of risk zones, traffic control, surveillance of all the involved subjects. Whoever attends the ward must follow the general risk prevention and mitigation measures. The application of this practical strategy can contribute to breaking the cycle of community-hospital-community transmission.